PELATIHAN PENYUSUNAN LAPORAN KEUANGAN LENGKAP BAGI MAHASISWA - randy kuswanto (Jurnal Abdi Mandala, 2022)
This community service program aims to increase accounting literacy for students who own and plan business activities. Financial records are a fundamental thing needed by all forms of business in order to obtain reliable financial information. Accounting as a financial discipline has an important role in producing this information. The participants of this activity are students who live in Taman Sari, West Jakarta. The activity was carried out for 4 months starting in February 2022 as many as 8 training sessions. The results of the training show that the participants' accounting understanding has an average of 92.3 which indicates the effectiveness of the training. The obstacle faced by students related to the accounting cycle is in the process of making general journals and adjustments. The results of this service are expected to improve public literacy regarding the importance of compiling financial information through accounting records